Thermal regime of paved embankment in permafrost regions along the Qinghai-Tibet Engineering Corridor. (5th September 2016) - Han, Fenglei; Yu, Wenbing; Yi, Xin; Hu, Da; Lu, Yan
Highlights: Numerical and statistic methods are used to study the thermal regime of embankment. The south-facing slope effect and other factors are considered. The mean annual air temperature is key factor determining the heat influence scope of embankment. The distance between the proposed and existed highway should be controlled to prevent the thermal interactions. Abstract: Heat influence among infrastructures is one of the key factors that will determine the route of the proposed Qinghai-Tibet Expressway (QTE) in the permafrost regions of the Qinghai-Tibet Plateau Engineering Corridor. Considering the south-facing slope effect and other factors, the dynamic variation of heat influence scope of paved embankment is investigated by numerical method and statistic approach. Results indicate that at the south-facing slope side heat influence scope at the horizontal direction is positive correlation with embankment height and pavement width, while it is negatively correlated with the mean annual air temperature (MAAT). At the north-facing slope side heat influence scope at the horizontal direction is positive correlation with pavement width, while it is negatively correlated with embankment height and the MAAT. After 50 years for the south-facing and north-facing slopes the maximum distance of heat influence scope from the foot of the embankment slope will be to 35.95 m and 31.84 m, respectively. The difference of heat influence scope at the horizontal direction between the south-facing and north-facing slope enlarges with increase of embankment height and pavement width. The grey-relation analyses show that the sensitivity of the heat influence scope to the factors is the MAAT, the embankment height and the pavement width in turn. The results are expected to serve as a reference for the design of the proposed QTE.